Acessibilidade e vulnerabilidade social: uma análise das calçadas no entorno de parques urbanos da cidade de Barueri, São Paulo, Brasil - Nonato, Ana Angélica (2024)
Introduction: This dissertation addresses the relevance of urban parks for the environment and human well-being, emphasizing that proper access to these spaces is crucial to ensure benefits. Despite physical proximity, inadequate sidewalks pose obstacles to mobility, especially in socially vulnerable areas, deepening socio-spatial inequalities. Objective: The aim of this dissertation is to analyze the quality and accessibility of sidewalks around urban parks located in areas with varying degrees of social vulnerability in the city of Barueri, São Paulo, Brazil. Method: An exploratory and quantitative approach is adopted, involving literature review, document analysis, geotechnologies, and field activities. Three parks were selected based on the Paulista Social Vulnerability Index. The diagnosis of sidewalks was carried out through the Sidewalk Quality and Accessibility Indices. Results: The study's results revealed a direct relationship between the condition of sidewalks and the level of social vulnerability in the surrounding area. The Municipal Park Dom José, in a low vulnerability area, exhibits better indices, while the Taddeo Cananeia Park, in a high vulnerability area, shows precarious conditions, emphasizing the need for an inclusive approach in urban planning. Conclusion: The findings indicate the urgency of investments and public policies to improve urban infrastructure, ensuring the adequacy of sidewalks to accessibility standards. The research also highlights the need for methodological adjustments in the Sidewalk Accessibility Index, suggesting a more detailed evaluation considering the conservation status of materials, for a precise understanding of barriers to accessibility and mobility in urban areas.